The quality of systematic reviews addressing peripheral nerve repair and reconstruction. Issue 3 (March 2019) - Sun, Beatrice J; Tijerina, Jonathan D; Agbim, Uchenna N; Lee, Gordon K; Nazerali, Rahim S
Summary: While systematic reviews are regarded as the strongest level of medical evidence, inconsistency in the quality and rigor of systematic reviews raises concerns about their use as a tool in guiding quality delivery in evidence-based clinical practice. The objective of this present study was to assess methodological soundness of systematic reviews with a particular focus on peripheral nerve repair and reconstruction. We performed a comprehensive search using PubMed and Scopus to identify all systematic reviews published on peripheral nerve reconstruction in 9 high-impact surgical journals. Two authors independently performed literature searches, screened abstracts, and extracted data. Discrepancies were resolved by discussion and consensus. The quality of systematic reviews was assessed using AMSTAR criteria. Initial search retrieved 184 articles. After screening duplicates, titles, abstracts, and conducting full text reviews, 26 studies met inclusion criteria. Of those, 18 (65%) were published by Plastic Surgery, 7 (27%) by Orthopedic Surgery, and 1 (4%) by Occupational Therapy. The total number of systematic reviews published on peripheral nerves each year has shown an increasing trend from 2004 through 2015. The overall median AMSTAR score was 5, reflecting a "fair" quality. There was no evidence of AMSTAR score improvement over time. Although the number of systematic reviews published on peripheral nerve repair has risen over the last decade, their quality has not exhibited the same increase. This highlights the necessity to increase familiarity with and conform to methodological quality criteria in order to improve the integrity of evidence-based medicine in peripheral nerve repair and reconstruction.